The effects of governance on shared prosperity in OIC countries/ Muhammad Fida'uddin Joharee - Joharee, Muhammad Fida'uddin (2018)
This study aims to identify the effects of governance on shared prosperity of the countries. This study focuses on OIC countries which are Malaysia, Pakistan, Jordan, Maldives and Indonesia for 10 years, started from 2007 until 2016. 5 countries have been chosen in this study. Generally, shared prosperity refers to the level income of the bottom 40% of the population. This study analyses the shared prosperity as dependent variable Which using income poverty as proxy, meanwhile the independent variables are political stability, regulatory quality, voice and accountability, control of corruption and government effectiveness. Hence, five independent Variables were used in this study to explain shared prosperity. This study using Ordinary Least Square (OLS) to run the data and meet all research objectives. The empirical findings of this study found that three of the independent variables which are political stability, regulatory quality and voice and accountability are significantly towards shared prosperity.